The Effects of Leadership Styles on Employee Motivation and Performance - Makwana, Bharat; Vidani, Dr. Jignesh (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the impact of leadership styles on employee motivation and performance (Vidani, 2015). It analyzes various behaviors—such as encouraging participation and inspiring a clear vision—and their influence on outcomes. Using Chi-Square analysis, the findings indicate that these relationships are weak and statistically insignificant, suggesting that leadership alone may not drive motivation and performance (Vidani, 2015). The results highlight the importance of other factors, such as organizational culture and individual traits, in shaping employee behavior (Solanki & Vidani, 2016). This challenges conventional leadership theories and advocates for a more holistic view of employee motivation within a broader organizational context (Vidani, 2015). The study recommends future research to explore mediating variables, adopt longitudinal approaches, and investigate non-leadership influences (Vidani, 2016)